Carving Books to Benefit Posterity: A Review of Publications by the Institute of Macao Studies, Jinan University - DAI, Guoqing (Journal of Research for Christianity in China (JRCC), 2025)
Under the leadership of Professor Ye Nong, the Institute of Macao Studies at Jinan University has dedicated itself to compiling literature and historical records centered on Macao during the Ming and Qing dynasties, focusing on the Maritime Silk Road. Beyond academic research, the institute has collaborated with publishing institutions in Macao and Guangzhou to produce series such as Maritime Silk Road Series. Since 2016, the institute has published over 30 academic works, including bibliographies, dictionaries, archives collections, Westerner's writings, inscriptions and image materials, monographs, translations, and policy-oriented reports. These publications vividly illustrate Macao’s role as a bridge in Sino-foreign cultural exchange, significantly advancing academic fields such as Macao Studies, Sino-foreign relations history, and Sinology.